Monoclonal antibodies for treatment of osteoporosis - Kroupová, Květa; Palicka, Vladimir; Rosa, Jan (Drugs of today, 2023)
Osteoporosis is a chronic disease with high unmet medical need. It is characterized by low bone mass and deteriorated bone architecture, leading to increased risk of fragility fractures, with vertebral and hip fractures representing the highest risk of morbidity and mortality. The baseline therapeutic approach to osteoporosis treatment has been based on adequate intake of calcium and supplementation of vitamin D. In this review, we focus on two approved monoclonal antibodies, romosozumab and denosumab, which have been shown to be efficient and safe options to prevent patient fractures. Romosozumab is a humanized monoclonal antibody IgG2 isotype that extracellularly binds sclerostin with high affinity and specificity. Denosumab is a fully human monoclonal antibody IgG2 isotype that binds RANK ligand (RANKL) and prevents the interaction of RANKL with its receptor RANK. Denosumab is an antiresorptive that has been used for more than a decade, and romosozumab has recently been approved for clinical practice worldwide.
Keywords: Immunoglobulin G; denosumab; osteoporóza; Humans; imunoglobulin G; lidé; Antibodies, Monoclonal, Humanized; Osteoporosis; Denosumab; humanizované monoklonální protilátky